Alien worm in worm: a new genus of endoparasitic polychaete (Phyllodocidae, Annelida) from scale worms (Aphroditidae and Polynoidae, Annelida). Issue 1 (16th July 2020) - Jimi, Naoto; Kimura, Taeko; Ogawa, Akito; Kajihara, Hiroshi
Abstract : Up to now, 19 species in eight genera and two families (Dorvilleidae and Oenonidae) of polychaetes are known to be endoparasitic in the body of other polychaetes. In this paper, we describe Endovermis seisuiae gen. et sp. nov. as the first representative of Phyllodocidae parasitizing other polychaetes. Specimens of E. seisuiae were found in the body cavity of Aphrodita sp. (Aphroditidae) and Lepidonotus sp. (Polynoidae) collected from muddy sediment, 216–218 m deep, off central Japan, the western North Pacific. Our multi-locus molecular phylogenetic analysis based on COI, 16S, 18S, and 28S sequences along with other phyllodocids for which sequences were available in public databases suggested that Endovermis as sister to the clade formed by Paranaitis Southern, 1914 and Eteone Savigny, 1922. urn:lsid:zoobank.org:pub:B4C50ABC-C3D5-4899-AAB6-1304FC08B0CF